"Primitive Sounds": An Examination of the Conflicting Discourse in the Early British Reception of Igor Stravinsky's Russian Ballets. Issue 2 (3rd April 2019) - Howerton, Rachel
ABSTRACT: Igor Stravinsky's ballet The Firebird was an immediate success upon its arrival in London in 1912. Nevertheless, as Stravinsky's music evolved with each subsequent ballet, his British reception equally evolved. While Stravinsky's supporters championed him as a new musical modernist, British conservative critics saw Stravinsky's music as a primitive threat to the traditional, nationalistic style that dominated nineteenth-century music. The analysis of both sides of the discourse that pervaded the early reception of Stravinsky's first three ballets in Britain – The Firebird, Petrushka, and The Rite of Spring – shows how these narratives helped shape Stravinsky's critical reception in twentieth-century Britain.